A new species of Parapharyngodon (Nematoda: Pharyngodonidae) infecting Dermatonotus muelleri (Anura: Microhylidae) from Caatinga, Northeastern Brazil - Filho, João A. De Araujo; Brito, Samuel V.; Almeida, Waltécio De O.; Morais, Drausio H.; Ávila, Robson W. (Zootaxa, 2015)
Parapharyngodon silvoi n. sp. (Nematoda: Pharyngodonidae) is described from the large and small intestine of the Muller’s termite frog Dermatonotus muelleri (Boettger, 1885) from the biome Caatinga, Exu municipality, Pernambuco State, Brazil, Dermatonotus muelleri is a fossorial species with a specialized termite diet, and feeding and reproductive behavior occurring only during the wet season. The new species is distinguished from other species of the genus Parapharyngodon by showing ovary not coiled around the esophagus, morphology of anterior cloacal lip, spicule size and number of caudal papillae.